Tourism development plan for the Calicoan Island: a community-based tourism (CBT) approach / Niña Jesusa P. Anore ... [et al.] - Anore, Niña Jesusa P.; Bersamin, Charmaigne Joy E.; Catapang, Issa Marie M.; Gatinga, Gil Ernest M.; Gomez, Ma. Angelica M.; Robles, Sophia Joy L.; Mercado, Jame Monren T. (Faculty of Hotel & Tourism Management, 2019)
This paper intends to analyse the perception of the stakeholders towards tourism development plan using community-based tourism approach in the case of Calicoan Island, Municipality of Guiuan, Eastern Samar. Data were collected by providing surveys for the locals and tourists and conducting an interview with the municipal mayor and the tourism officer of Guiuan. For this tourism development plan using the community based-tourism approach, the perception of the tourists and locals were identified and analysed. From the paper, it has been found that Calicoan is still a very raw island. Although the island has its limits to its tourism products such as accommodation, goods, and other services, Calicoan Island is a tourist destination with great potential and a lot of opportunities in different factors. Calicoan Island will be able to achieve success if it is properly organised by the tourism industry.